Digital forensics and watermarking : 16th International Workshop, IWDW 2017, Magdeburg, Germany, August 23-25, 2017, Proceedings /: 16th International Workshop, IWDW 2017, Magdeburg, Germany, August 23-25, 2017, Proceedings. ([2017]) - Unknown
No abstract available